Integration of MgAl-layered double hydroxides into TiO2 nanorods as photoanodes for enhanced photoelectrochemical water splitting - Yanjun Wang; Zhengyang Zhang; Shiwei Wang; Minmin Han (Catalysis Communications, 2022)
The slow development of photoelectrochemical (PEC) water splitting mainly results from the inefficient separation and transfer of photogenerated carriers. Herein, we fabricated a core-shell nanostructure by loading MgAl-layered double hydroxide (MgAl-LDH) nanofilms on the surface of TiO2 nanorods with a simple dip-coating method. The PEC performance was adjusted by controlling the immersion time, and TiO2/MgAl-LDH photoanode with an immersion time of 8 h achieved an optimal photocurrent density of 1.16 mA cm−2, which is 116 times that of TiO2. The improved interfacial charge transfer and reduced recombination loss of photogenerated electron-hole pairs account for the excellent performance.